Домашние животные: [0+] / художник И. Н. Приходкин - Зверькова Юлия Викторовна (Первый учебник малыша, 2018)
Экземпляры: ф.28 (20190712) / Инвентарный номер: 063111 / Цена: 41.00 / Авт.знак: З-43 / ГРНТИ: 14.23.09 / ББК: 74.102